2010
DOI: 10.1111/j.1365-313x.2010.04179.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic pyruvate,orthophosphate dikinase functions in nitrogen remobilization during leaf senescence and limits individual seed growth and nitrogen content

Abstract: SUMMARYThe protein content of seeds determines their nutritive value, downstream processing properties and market value. Up to 95% of seed protein is derived from amino acids that are exported to the seed after degradation of existing protein in leaves, but the pathways responsible for this nitrogen metabolism are poorly defined. The enzyme pyruvate,orthophosphate dikinase (PPDK) interconverts pyruvate and phosphoenolpyruvate, and is found in both plastids and the cytosol in plants. PPDK plays a cardinal role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 52 publications
3
108
0
2
Order By: Relevance
“…It has also been associated with suppressed phosphoenolpyruvate carboxykinase activity (Osterås et al, 1997) and salt stress (Fisslthaler et al, 1995). Recently, this enzyme has been shown to play an important role in N remobilization (Taylor et al, 2010). Likewise, the transcript abundances for enzymes of the pentose phosphate cycle predicted to be localized in the cyto-sol, Glc-6-P 1-dehydrogenase and phosphogluconate dehydrogenase (decarboxylating), were increased under those conditions.…”
Section: General Changes In Primary Metabolismmentioning
confidence: 78%
“…It has also been associated with suppressed phosphoenolpyruvate carboxykinase activity (Osterås et al, 1997) and salt stress (Fisslthaler et al, 1995). Recently, this enzyme has been shown to play an important role in N remobilization (Taylor et al, 2010). Likewise, the transcript abundances for enzymes of the pentose phosphate cycle predicted to be localized in the cyto-sol, Glc-6-P 1-dehydrogenase and phosphogluconate dehydrogenase (decarboxylating), were increased under those conditions.…”
Section: General Changes In Primary Metabolismmentioning
confidence: 78%
“…This transcript encodes the cytosol-localized form of PPDK (Parsley and Hibberd, 2006) that is suggested to be important during amino acid remobilization and senescence (Taylor et al, 2010) and for gluconeogenesis (Eastmond et al, 2015). Interestingly, several other genes involved in gluconeogenesis were quantitatively up-regulated or down-regulated in response to the compound and darkness treatments (Supplemental Fig.…”
Section: Conserved As Events Indicate An Additional Layer Of Regulatimentioning
confidence: 99%
“…During flowering, the vegetative plant segments switch from being sink organs to source organs, with associated modifications in the N fluxes from older to younger tissues and to the reproductive organs (Le Deunff and Malagoli 2014). Labeling studies in Arabidopsis thaliana (Taylor et al 2010) and B. napus (Rossato et al 2001;Malagoli et al 2005a) showed that the N accumulated in the seeds at harvest originates mainly from the degradation of proteins in vegetative plant segments. phase sequentially, multiple overlapping source-sink situations are possible in rapeseed.…”
Section: The Post-anthesis Nitrogen Balance Between Source Organs Andmentioning
confidence: 99%